(3TQM YUGe GdOjf GdESaQGjjfi Ydi GdQSGdI GdYVOjIs - (3EHQGgje Hf eMeO Hf YQH TGg GdESaQGjjfj, YUGe GdOjf , GdYUGe GdESaQGjjfj,J (B945 (3g` s; (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf GdMeO ddg QH GdYGdejf gPg ddEjeGA Edi GdeYGfi GdeQJHI GdehLhOI ai GdJYbd abW s
(3BNQgG (B:s
(3hai Xfg hUakG dGjOaYg bhdg EP GdeYJHQ GdhVY hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH JeJ GdQSGdIGdTQjaI GdeSeGg HYUGe GdOjf GdhGbYI Ydi GdQSGdI GdYVOjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs